Circulating metabolites of Borneolum syntheticum (Bingpian) ameliorate atherosclerosis in ApoE−/− mice via inhibiting macrophage foam-cell formation - He, Rong-rong; Ma, Chuan-rui; He, Xin; Dong, Yan-xi; Li, Hui; Chu, Zi-xuan; Yang, Xi-he; Wang, Jia-qi; Wang, Ting; Wang, Feng-qing; Du, Fei-fei; Rao, Ying; et al. (Acta pharmacologica Sinica, 2025)
Translational pharmacological research on traditional medicines lays the foundation for precisely understanding how the medicines function in the body to deliver therapeutic benefits. Borneolum syntheticum (Bingpian) is commonly used in Chinese herbal medicines for coronary heart disease, but its specific cardiovascular impact remains poorly understood. Isoborneol, a constituent of Bingpian, has been found to reduce lipid accumulation in macrophages in vitro, but its oral bioavailability is limited. This investigation aimed to evaluate anti-atherosclerotic effects of Bingpian, based on understanding its first-pass metabolism. Human subjects orally received an herbal medicine containing Bingpian and their plasma samples were analyzed to identify the major circulating compounds of Bingpian, with the metabolism that was also characterized in vitro and in mice. The identified compounds were evaluated for their ability to inhibit macrophage foam-cell formation induced by oxidized low-density lipoprotein. Furthermore, the anti-atherosclerotic effect of repeatedly dosed Bingpian was assessed in ApoE −/− mice fed a high-fat diet. In human subjects, the major circulating compounds of Bingpian were metabolites, rather than their precursor constituents borneol and isoborneol. These constituents were efficiently absorbed in the intestinal tract but underwent significant first-pass metabolism, involving UGT2B7-mediated glucuronidation into borneol-2- O -glucuronide and isoborneol-2- O -glucuronide, respectively, and CYP2A6/2B6/3A-mediated oxidation both into camphor. Despite their poor membrane permeability, hepatic efflux of borneol-2- O -glucuronide and isoborneol-2- O -glucuronide into the systemic circulation was enhanced by MRP3/4. The circulating metabolites, particularly their combinations, markedly inhibited macrophage foam-cell formation induced by oxidized low-density lipoprotein in vitro. Sub-chronic administration of Bingpian (30 mg·kg −1 ·d − 1 , i.g.) for 12 weeks significantly decreased atherosclerotic lesion size and enhanced plaque stability in ApoE −/− mice. Systemic exposure to Bingpian metabolites in mice closely resembles that in humans, suggesting that the pharmacodynamic effects of Bingpian in mice are likely applicable to humans. Overall, the cardiovascular benefits of Bingpian involve reducing atherosclerosis by inhibiting foam-cell formation through its metabolites. This investigation supports that oral Bingpian could be a druggable agent for reducing atherosclerosis.